The relationship between school belonging and depressive symptoms among Chinese college students: a moderated mediation model - Yun, Ai; Cai, Yi; Li, Shuang; Ch. B., Isakova; Cen, Guanyu; Hu, Yuanyan (Frontiers in Psychology, 2026)
ObjectiveTo explore the relationship and mechanism between school belonging and depressive symptoms among Chinese college students.MethodsA total of 440 Chinese college students were surveyed using the Chinese version of the Psychological Sense of School Membership Scale (PSSM-CR), the Short Version of the Center for Epidemiologic Studies Depression Scale (CESD-10), the Self-Consistency and Congruence Scale (SCCS), the Schutte Self-report Emotional Intelligence Scale (SSEIS-C).Results(1) School belonging, self-consistency and congruence, and depressive symptoms were significantly correlated (r = −0.53 to 0.74, p < 0.01); (2) Self-consistency and congruence played a partial mediating role in the relationship between school belonging and depressive symptoms among Chinese college students; (3) Emotional intelligence significantly moderated the first half of the mediating model: the first half of the mediating model was significant in both the low emotional intelligence group and the high emotional intelligence group.ConclusionSelf-consistency and congruence and emotional intelligence play a moderated mediation role in the relationship between school belonging and depressive symptoms among Chinese college students.